A two-dimensional porous framework: solvent-induced structural transformation and selective adsorption towards malachite green. Issue 26 (19th June 2017) - Li, Huanzhi; Fang, Xueting; Ma, Sha; Niu, Yanfei; Zhao, Xiaoli; Xu, Jiaqiang; Duan, Zhiming
Abstract : A two-dimensional porous frameworkSHU-1 could undergo solvent-induced structural transformations toSHU-1a in methanol andSHU-1b in water.SHU-1, SHU-1a andSHU-1b showed selective adsorption towards malachite green. Abstract : A two-dimensional porous frameworkSHU-1 could undergo solvent-induced structural transformations toSHU-1a in methanol andSHU-1b in water.SHU-1, SHU-1a andSHU-1b showed selective adsorption towards malachite green.